A macrophage uptaking near-infrared chemical probe CDnir7 for in vivo imaging of inflammation - Kang, Nam-Young; Park, Sung-Jin; Ang, Xiao Wei Emmiline; Samanta, Animesh; Driessen, Wouter H. P.; Ntziachristos, Vasilis; Vasquez, Kristine O.; Peterson, Jeffrey D.; Yun, Seong-Wook; Chang, Young-Tae (Chemical Communications, 2014)
Visualization of macrophages in live animals has been of great interest for a better understanding of inflammation. We developed a near infrared (NIR) probe CDnir7 that can selectively detect macrophages and visualize inflammation in vivo using the IVIS spectrum, Fluorescence Molecular Tomography (FMT) and Multi-Spectral Optoacoustic Tomography (MSOT). © The Partner Organisations 2014.
CRIS-Team Scopus Importer:2023-03-08